In-Vitro Cytotoxic Evaluation of Titanium Dioxide Nanoparticle Using L929 Cell Lines - Mahesh R; Dinesh S.P. Saravana; Rajeshkumar S; Amalorpavam V (Wolters Kluwer Medknow Publications, 2024)
Tooth movement in orthodontic therapy is connected to the frictional force that is created as the wire passes over the bracket. It is possible for teeth to move quickly when friction is at a minimum. Wires coated with nanoparticles have been found to reduce friction as a result of current developments in the orthodontics sector. Having an antimicrobial property is an added benefit. To reduce the friction generated by brackets, wires, and bands by lessening their cytotoxicity, this study examines the potential use of TiO2 nanoparticles in orthodontics. A monolayer of L929 was utilized in an indirect cytotoxicity test to evaluate the cytotoxicity of the coated orthodontic wire. The absence of reactive zones in our sample data demonstrates that TiO2 is not cytotoxic. Considering the results of our study, we conclude that TiO2 is secure for use as a coating for orthodontic devices.